2018
DOI: 10.1159/000487094
|View full text |Cite
|
Sign up to set email alerts
|

Use of Array Comparative Genomic Hybridization for the Diagnosis of DiGeorge Syndrome in Saudi Arabian Population

Abstract: DiGeorge syndrome (DGS) is a genetic disorder known as a clinically variable syndrome with over 180 associated phenotypic features. It is caused by a common human deletion in the 22q11.2 chromosomal region and currently is affecting approximately 1 in 4,000 individuals. Despite the prevalence of inherited diseases mainly due to consanguineous marriages, the current diagnosis of DGS in Saudi Arabia is mainly based on conventional high-resolution chromosome banding (karyotyping) and FISH techniques. However, adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Seven high-risk cases were regarded as FPs. That is, the current aCGH might not detect all deletions in the critical region [27]. Third, further confirmation of low-risk group was absent due to clinical practice.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Seven high-risk cases were regarded as FPs. That is, the current aCGH might not detect all deletions in the critical region [27]. Third, further confirmation of low-risk group was absent due to clinical practice.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The fact that hypocalcemia was not found in the clinical 22q11.2DS patients can be interpreted as this finding does not lead to initial consideration of 22q11.2DS by physicians. Similarly, (14). In another study involving 347 patients, the diagnosis rate by FISH and MLPA analysis was 28.2% (13).…”
Section: Discussionmentioning
confidence: 92%
“…The diagnostic application of array-CGH in Saudi DD/CM/ID patients, to the best of our knowledge, has not been reported yet. However, a few studies have reported the application of array-CGH in the identification of disease-causing variants such as recurrent spontaneous abortion in Saudi Arabia [ 24 ], juvenile myoclonic epilepsy [ 25 ], acute myeloid leukemia [ 26 ], Lynch Syndrome [ 27 ], gastric cancer [ 28 ], Williams’ syndrome [ 29 ], DiGeorge Syndrome [ 30 ], and congenital heart disease [ 31 ]. Hence, in the present study, we aimed to investigate the genetic heterogeneity in Saudi children with DD/CM/ID.…”
Section: Introductionmentioning
confidence: 99%